Localized surface plasmon resonance sensing of hydrogen sulfide using zinc oxide film - Yuki Takimoto; Keiji Komatsu; Hiromasa Namiki; Kazuto Mochizuki; Tomoe Nakagawa; Kohki Nagata; Kazuki Komiya; Tomoko Gessei; Akira Monkawa (Scientific Reports)
Abstract A localized surface plasmon resonance (LSPR) sensor for hydrogen sulfide (H2S) has been developed by coating a gold nanopattern with zinc oxide (ZnO) film. H2S detection was achieved by monitoring changes in absorbance at a specific wavelength in the LSPR spectrum. The absorbance increased during exposure to H2S and remained constant after H2S ceased. These responses indicate that the sensor can measure the integrated concentrations of H2S. The sensitivity to H2S was enhanced with increasing relative humidity, enabling detection of 0.05–3 ppm H2S within 10 min at 70% relative humidity. The sensor’s sensitivity and LSPR spectrum could be restored by heating it at 500 °C in air. Notably, the sensor did not respond to methyl mercaptan or dimethyl sulfide, demonstrating high selectivity for H2S. This study highlights the potential of the ZnO-deposited LSPR sensor for highly sensitive and selective detection of H2S.